2012
DOI: 10.3109/08923973.2012.738688
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin induces apoptosis in human cervical cancer cell line HeLa cells

Abstract: Amygdalin, a naturally occurring substance, has been suggested to be efficacious as an anticancer substance. The effect of amygdalin on cervical cancer cells has never been studied. In this study, we found that the viability of human cervical cancer HeLa cell line was significantly inhibited by amygdalin. 4,6-Diamino-2-phenyl indole (DAPI) staining showed that amygdalin-treated HeLa cells developed typical apoptotic changes. The development of apoptosis in the amygdalin-treated HeLa cells were confirmed by dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 30 publications
9
61
0
4
Order By: Relevance
“…Moreover, our results showed that the amygdalin is efficiently induced to the inhibition of cell growth at ∼10 mg/ml concentration as reported in the previous studies (Shragg et al 1982;Chen et al 2013;Makarević et al 2014aMakarević et al , 2014b. However, we interestingly found that the normal somatic cells (MCR-5 fibroblasts) show considerable resistance to the cell growth and senescence at 10 mg/ml concentration of amygdalin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, our results showed that the amygdalin is efficiently induced to the inhibition of cell growth at ∼10 mg/ml concentration as reported in the previous studies (Shragg et al 1982;Chen et al 2013;Makarević et al 2014aMakarević et al , 2014b. However, we interestingly found that the normal somatic cells (MCR-5 fibroblasts) show considerable resistance to the cell growth and senescence at 10 mg/ml concentration of amygdalin.…”
Section: Discussionsupporting
confidence: 90%
“…Cell growth and proliferation were dose-dependently induced in UMUC-3, RT112 and TCCSUP bladder cancer cell lines treated with amygdalin, resulting in arrest of cell cycle progression by down-regulation of cdk2 and cyclin A (Makarević et al 2014a), and amygdalin treatment to SNU-C4 human colon cancer cells also displayed anticancer effect via down-regulation of cell cycle-related genes, implying that the amygdalin compound is induced to incomplete DNA synthesis (Park et al 2005). Furthermore, it has been demonstrated that apoptosis is induced by up-regulating caspase-3 activity and pro-apoptotic Bax protein, whereas down-regulating anti-apoptotic protein Bcl-2 in the amygdalin-treated HeLa cells (Chen et al 2013), human DU145 and LNCaP prostate cancer cells (Chang et al 2006). In another study, it has been shown that amygdalin influences the decrease in adhesion and migratory properties of UMUC-3, TCCSUP and RT112 bladder cancer cells by Figure 5.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Aghadavod [52] yaptığı literatür incelemesinde, amigdalinin damar sertliği ve şeker hastalığının tedavisinde ve kanser oluşumunun önlenmesinde pozitif etkiye sahip olduğu sonucuna ulaşmıştır. Diğer taraftan amigdalinin antikanserojen etki göstermediği, parçalanma ürünlerinden bazılarının böyle bir aktiviteye sahip olduğu belirlenmiştir [59]. Song ve Xu [19] tarafından amigdalinin tümör hücreleri üzerine etkili olduğu ancak etki mekanizması üzerinde yeterli çalışmanın bulunmadığı ifade edilmiştir.…”
Section: Tedavi Edici Etkisiunclassified
“…This article is available from: http://www.acanceresearch.com/ standards, regardless of all this Americans use it as drug for cancer treatment [11,12].…”
mentioning
confidence: 99%